(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This comparative analysis explores the concept of happiness as expressed in the Uzbek and English languages, highlighting the cultural nuances and values that shape these expressions. By examining terms, idioms, and proverbs related to happiness, the study reveals both similarities and differences in how these cultures understand and articulate this universal human experience.